Correlation between HbA1c and lipid profile in diabetes: a primary health concern in Aseer, Saudi Arabia - Fatima Riaz; Archana Nimesh (Universitas Ahmad Dahlan, 2023)
Background: Type 2 diabetes mellitus (T2DM) presently affects 537 million adults globally. It has a high prevalence in the Saudi population (31.6%), ranking 2nd highest in the Middle East and 7th worldwide. T2DM is characterized by insulin resistance and hyperglycemia, causing the glycation of hemoglobin, plasma proteins, tissue proteins, and their receptors. The high insulinemic state leads to dyslipidemia. These biochemical alterations can cause complications like atherosclerosis, coronary artery disease, angina, myocardial infarctions, and hypertension. Considering the high prevalence of diabetes in the Saudi population and the lack of studies conducted at primary health care (PHC) centers in Saudi Arabia, this study was done to investigate the status of diabetes control in T2DM patients and propose appropriate measures to prevent the development of future complications. Method: This cross-sectional study recruited 191 known T2DM patients presenting at the PHC center in the Al Qabil locality of Aseer province of Saudi Arabia. The patient's demographic and glycemic and lipid profile data were recorded and statistically analyzed. Results: T2DM was more prevalent in males. T2DM patients were found to be obese, and 52% had coexisting hypertension. Patients had deranged glycemic profiles and dyslipidemia despite taking hypoglycemic agents. Hyperglycemia and dyslipidemia were significantly higher in people with diabetes having HbA1c > 7. HbA1c is correlated with dyslipidemia, and dyslipidemia is linked considerably with obesity. Conclusion: T2DM patients must be regularly followed up to ensure drug compliance, explained about foreseen medical complications, and motivated to adopt lifestyle modification measures to control their weight, BP, and blood glucose.